Study on mechanism and factors affecting the gas leakage through clearance seal at nano-level by molecular dynamics method. (1st May 2016) - Qi, Yingxia; Meng, Xiangqi; Mu, Defu; Sun, Yangliu; Zhang, Hua
Abstract: The past researches on the gas leakage through the clearance seal were studied mainly by the analytical model or numerical simulations using CFD method based on the classical fluid mechanics theory in the conditions of steady laminar flow, incompressible, constant temperature, constant viscosity, and no relative sliding between the inner and outer wall. However, it is widely known that the CFD theory may not be applicable to the micro-size flow. In this paper, the molecular mechanism of the gas leak through the clearance seal was investigated by MD (molecular dynamics) simulations. The Johnson potential model was used for Fe–Fe atomic interactions and the UFF (Universal Force Field) potential model was used for the atomic interactions between Fe–He and He–He. The gap thickness was varied from 2000 Å to 5000 Å. The pressure difference over the ends of the gap was from 0.2 MPa to 1.0 MPa. The simulation results show that the leakage rate was proportional to the pressure difference and the gap thickness. During the process of the leakage, the sticky layers were formed on the gap walls. The number density of the atoms in the sticky layer was much larger than that of the central region. And the density of the gas flow of the leakage was much smaller than that of the gas reservoir. The leakage mechanism was mainly due to the diffusion motions of the atoms through the sticky layers although the moving speed of the sticky layers was very slow. The leakage flow rate from the MD simulation was quite consistent with that from the analytical calculation. Highlights: The mechanism of gas leakage was firstly revealed. The leakage rate was proportional to the gap thickness. The leakage rate was proportional to the pressure difference. The density of leakage gas flow was not same as that of the gas reservoir. The sticky layers were formed on the gap walls.